Implementation of Community-Based Natural Disaster Risk Reduction Policy in Minahasa Regency - Kaumpungan, Novrike Stanly Johan; Pangkey, Itje; Mamonto, Fitri (Technium Social Sciences Journal, 2025)
This study aims to find out, describe, analyze, and explain the implementation of community-based natural disaster risk reduction policies in Minahasa Regency based on Government Regulation No. 21/2008, as well as identify the factors that influence it. The research method used is descriptive qualitative, with data collection techniques through interviews, observation, and documentation. The results showed that the implementation of community-based natural disaster risk reduction policy in Minahasa Regency has not run optimally. Several obstacles were found in the implementation of socialization activities, such as the uneven implementation of socialization in all regions, limited access to online socialization, and the lack of regulatory, budgetary and personnel support. In training activities, weak coordination between institutions was identified, the implementation of training in disaster-prone areas was not optimal, and the technical planning of the program was not optimal. Meanwhile, in the rehearsal and simulation activities, there are still areas that have not carried out these activities, the lack of a disaster awareness culture in the community, and the lack of government follow-up on program sustainability. These findings indicate the need for improvement in the aspects of planning, coordination and resource support so that the community-based disaster risk reduction policy in Minahasa Regency can be implemented effectively and sustainably.